Preliminary Characterization of a Monoclonal Antibody (AS-2) against Cell Cycle Related Proteins - Stefano Nigro; Anna Rapallo; Angela Di Vinci; Elio Geido; Roberto Orecchia; Walter Giaretti (Analytical Cellular Pathology)
A monoclonal antibody (AS-2) raised by using isolated nuclei from a human erythroleukemia cell line as immunogen is described.